Гончарні вироби із с. Дибинці у зібранні Полтавського краєзнавчого музею імені Василя Кричевського: до питання атрибуції та реставрації - Кондратенко, Н.Г. (Сіверщина в історії України, 2021)
Стаття присвячена вивченню музейної колекції гончарних виробів, що походять із с. Дибинці на Київщині, яке славилося своїми гончарями ще з XVIII ст. і стало осердям гончарного центру,
що об’єднав довколишні населені пункти. У статті наводиться повний перелік музейного зібрання, яке налічує 20 предметів.
Розглядаються морфологічні та типологічні особливості посуду.
Найчисленнішу групу предметів становлять миски. Їх розподілено за формою та розміром. Усю колекцію також проаналізовано
за типом декорування. Виокремлено групи посуду, прикрашені зображеннями тварин, рослин та геометричним орнаментом. Особливу увагу приділено питанню реставрації дибинського посуду
співробітниками Полтавського краєзнавчого музею імені Василя
Кричевського, спираючись на значну історичну цінність та високий експозиційний потенціал. The article is dedicated to studying museum collection of pottery
items that originate from Dybyntsi in Kyiv Region, famous for its potters since the 18th century as it became the pottery center, which united
neighbor villages. During 1807–1828 faience factory of the Branytsky
Brothers worked here. More than one hundred of local potters worked
there. Since the second half of the 19th century clay dishes and fire resisting
bricks from Dybyntsi were sold far beyond the region. At the early
20th century art ceramics of Dybyntsi potters won the first prize in
Kyiv Region. In 1913 works of local masters – Kalenyk Masiuk, Yelysei
Protsenko, Borys Breus, Kyrylo Rodak, Zosym and Yatrop Masiuk –
were marked at All-Russian home-produced exhibitions in Kyiv and
Saint-Petersburg. Complete list of the gathering is given. It includes 20
objects – bowls, gourds, pots, cup, lid, jars, “makitra” (pot for grinding
poppy seeds), “bynchyk” (jar with handle above). Short review of
history of Dybyntsi ceramic collection in museum forming is given. As
during the Second World War (1939–1945) most of funds documents
were lost in the ruining fire, which almost destroyed the museum building
and part of its collection, it is difficult to find out concrete source
of each object coming. Though according to preserved numbers at seven
bowls we can get to know, that they originate from the collection of
the private museum of Kateryna Skarzhynska in Kruhlyk village Lubny
district. She gave her gathering to the Museum of Poltava Huberniia
Zemstvo in 1906.
Their morphological and typological peculiarities of dishes are observed.
The most numerous group unites bowls. They are divided according
to their form and size. The whole collection is also analyzed according
to type of decoration. Groups of items decorated with pictures
of animals, plants and geometrical elements are outlined.
Special attention is paid to restoration of Dybyntsi dishes by conservators
from the Vasyl Krychevsky Poltava Local Lore Museum, minding
their great historical value and expositional potential.